Professionalism in medical education at Universidad Nacional Mayor de San Marcos. A study of syllabi - Sogi, Cecilia (2015)
Objective. To identify teaching of professionalism (excellence, humanism, accountability and altruism) in the medical curricula of the Universidad Nacional Mayor de San Marcos. Design. Qualitative, specifically encoded qualitative study. Setting. Faculty of Medicine, Universidad Nacional Mayor de San Marcos, Lima, Peru. Material. Medical education syllabi. Methods. Thirty-eight syllabi of courses corresponding to the six years of medical education were examined. A panel of experts was settled and the content analysis method was used. The inter-rater reliability was established and principles of professionalism were identified in competencies, contents, teaching methods and syllabi assessment. Main outcome measures. Teaching of professionalism. Results. Fifty-eight per cent of courses mentioned some elements of professionalism; the most frequent competencies were related to excellence followed by humanism and accountability. Contents did not refer to professionalism except in a few courses. The teaching methods of some courses explicitly mentioned teachers’ role model and learning of professional conduct in clinical practice. Evaluation was through cognitive assessment and teachers’ score assessing students’ practice and other activities. Conclusions. Excellence, humanism and accountability were present more frequently in competence and teaching methodology and less frequently in content and course assessment.